The Role of Village Government in Overcoming Conflicts in Residents' Fights Due to Alcohol in Aibura Village - Danar Aswim; Petrus Kpalet; Theresia Afilanti (Journal Civics And Social Studies, 2021)
This research aims to determine the role of the village government in resolving community brawl conflicts caused by alcohol and to determine the effectiveness of the village government's role in resolving community brawl conflicts caused by alcohol in Aibura Village, Waigete District, Sikka Regency. Area. The research subjects were Village Service Officers, BPD Secretaries and Traditional Leaders. Researchers use a qualitative approach. The data collection techniques used are observation, interviews and documentation techniques. The data analysis techniques used in this research are data collection, data reduction, and drawing conclusions. The results of the research state that the role of the village government is to use mediation patterns and the customary law of guni gelo, which means that payments from victims to perpetrators are a conflict resolution process as stated in the Call for Settlement of Customary Law. And Minutes about the effectiveness of the village government in dealing with community conflicts caused by alcohol. This settlement was carried out effectively by the Aibura Village Government by providing adequate infrastructure, including the BPD Chair, traditional leaders, village peace judges, hamlet heads, RT/RW heads, Linmas members, perpetrators, victims, meeting places or locations. From the results of the research, the author concludes that the government's role is expected to be maximized in providing socialization about alcohol and providing education to the community about health and psychology so that people know the impact of consuming alcohol and it is also hoped that the Aibura Village Government will make village regulations regarding alcohol.